Terrestrial Heat Flow and Lithospheric Thermal Structure Characteristics in Nanping City of Hainan - Xiaoxue Yan; Xiaolin Wang; Guicheng Xue; Ruoxi Yuan; Feng Yang (Energies, 2024)
The Nanping geothermal field in Hainan is situated within the Wuzhi Mountain fold belt of the South China fold system based on its geotectonic units. Although there is abundant surface heat detected and widespread distribution of Late Mesozoic granite in the area, the geological background of geothermal resources remains unclear. In this article, we collected core samples from boreholes within the Nanping geothermal field to conduct testing and analysis on rock thermal conductivity and heat-production rate. By combining these results with temperature logging data, we discuss a method for diterming the heat flow background of convective geothermal system. Furthermore, the study analyzed the geothermal flux and deep thermal structure of the research area. The results demonstrate that the average radioactive heat production rate of the Baocheng rock mass in the study area is 3.16 μW/m³, primarily attributed to the decay heat of Th and U, while the heat contribution of K is negligible. The thermal conductivity values of the rocks are relatively high, ranging from 2.29 to 3.75 W/(mK), slightly exceeding the average thermal conductivity of the upper crust. The study area represents a typical convective geothermal field influenced by groundwater convection, exhibiting a high geothermal temperature gradient. Using the groundwater-correction method, the geothermal flux in the study area is calculated to be 89–108.27 mW/m², of which the thermal conduction component is 73.17 mW/m² and the convective component is 15.83–35.1 mW/m². Among these components, heat generated from radioactive decay of crustal radioactive elements contributes 35.44 mW/m² to thermal conduction, while deep mantle conduction accounts for a heat flux is 37.73 mW/m², with a ratio of 1:1.07 between them. The difference between crustal and mantle heat fluxes is minimal in this region, indicating an approximation towards a “crust-mantle heat source balance zone”. Furthermore, the thickness of the “hot” lithosphere in the study area ranges from 42 to 46 km, indicating significant characteristics of extension-thinning.